Characterization of introduced breed of sheep and pattenl of conservation of Sumatera thin tail (STT) sheep in North Sumatera - Priyanto D; A.R Siregar; E Handiwirawan; Subandriyo . (Indonesian Center for Animal Research and Development (ICARD), 2000)
Sumatera thin tail (STT) sheep are highly adapted to the local environment, no seasonal reproductive activity, and highresistance to internal parasite, but they have small body size and low mature body weight.